Strategic Delegation in Experimental Markets - Steffen Huck; Wieland Müller; Hans-Theo Norman (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this experiment, we analyze strategic delegation in a Cournot duopoly. Owners can choose among two different contracts which determine their managers' salaries. One contract simply gives managers incentives to maximize firm profits, while the second contract gives an additional sales bonus. Although theory predicts the second contract to be chosen, it is only rarely chosen in the experimental markets. This behavior is rational given that managers do not play according to the subgame perfect equilibrium prediction when asymmetric contracts are given.
Keywords: 330; Strategic delegation; managerial incentives; experimental economics